2019
DOI: 10.1016/j.seizure.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Substitution has better efficacy than add-on therapy for patients with focal epilepsy after their first antiepileptic drug treatments fail

Abstract: A B S T R A C TPurpose: This study is to compare the efficacy of substitution with add-on therapy in patients with focal epilepsy, whose first monotherapy has failed after receiving usual treatments. Methods: This is a prospective, long-term, non-randomized observational cohort study. Data were collected from Wenzhou Epilepsy Follow Up Registry Database. Focal epilepsy patients from January 2003 to June 2015, whose first monotherapy had failed, were registered. The total observation period was three years. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In this pragmatic study, the treating neurologists chose to add clobazam as per their own discretion. Similar to our study, seizure freedom rates ranging from 50% to 60% after the failure of initial monotherapy have been reported by other observational studies [26,27]. Although a seizure freedom rate of >70% should be evaluated in the context of nonblinded observational nature of study, it does provide preliminary evidence that clobazam is an effective drug as first add-on therapy.…”
Section: Discussionsupporting
confidence: 89%
“…In this pragmatic study, the treating neurologists chose to add clobazam as per their own discretion. Similar to our study, seizure freedom rates ranging from 50% to 60% after the failure of initial monotherapy have been reported by other observational studies [26,27]. Although a seizure freedom rate of >70% should be evaluated in the context of nonblinded observational nature of study, it does provide preliminary evidence that clobazam is an effective drug as first add-on therapy.…”
Section: Discussionsupporting
confidence: 89%
“…These trial designs, despite their shortcomings, provide evidence of efficacy of a substitution approach in DRE and have led to several ASMs being approved for use as monotherapy. Randomized studies comparing add‐on to substitution in patients with relatively newly diagnosed focal epilepsy failing initial ASM monotherapy have shown no difference in seizure outcomes, 30,31 but some observational studies suggest that substitution is associated with better seizure outcome and retention rate 32 . Prospective observational studies assessing remission in DRE cohorts do not explicitly analyze seizure outcomes by mode of drug introduction, 2,3 but one recent longitudinal cohort study showed no differences in the two approaches 26 …”
Section: Discussionmentioning
confidence: 99%
“…Initial treatment with ASM monotherapy is standard; however, ASM conversion may be required when the initial drug fails, either due to lack of efficacy or tolerability [48,51]. Although the benefits of substitution over add-on therapy are still a matter of debate [17,[52][53][54][55], a trial with one or more additional monotherapies is common before starting chronic polytherapy.…”
Section: Monotherapy Conversionmentioning
confidence: 99%